BIOLOGY HABITS AND DISTRIBUTION IN ANTIOQUIA OF CHINCHE DE ENCAJE Dictira monotropidia STAL (Hemiptera: Tingidae) en nogal cafetero (Cordial alliodora (Ruíz & Pavon Cham). - MADRIGAL-C., ALEJANDRO (Revista Colombiana de Entomología, 1987)
The nogal cafetero (C. alliodora) is one of the species with more future in the forest activity in Colombia because of the very good quality of the wood and its adaptability to a wide rank of weather and soil conditions. This work studied the biology, habits, and distribution of the lace bug D. monotropidia (Hemiptera: Tingidae) in the Antioquia department. This insect is very harmful and closely associate with C. alliodora. The D. monotropidia life cycle took 45.89 days, distributed as follows: eggs 24.10 days; nymphs 21.39 days ( 2.2, 4.06, 4.18, 4.10, and 6.43 days for the first, second, third, fourth and fifth nymphal instars respectively). The females incrust the eggs in a single group (45.49 eggs average) in the main nervadura by the undersurface of the leaves. The females take care of the eggs until they hatch. The nymphs remain together in the undersurface of the leaves until they become adults.